Dermoscopic differentiation of pustular psoriasis and tinea incognito - Balachandra S Ankad; Apoorva S Reshme; Balakrishna P Nikam; Nicholas D Drago (Wolters Kluwer Medknow Publications, 2020)
Introduction: Dermoscopy is a rapid diagnostic method in many inflammatory dermatoses which are diagnosed accurately by dermoscopy. Clinically, pustular psoriasis (PP) and tinea incognito (TI) look similar, and sometimes, TI is an invader into PP. Hence, it is important to differentiate each to manage them properly. Thus, a tool to distinguish both TI and PP is necessary for the correct diagnosis and management. Dermoscopy of PP is well-documented but not in TI. Here, we describe the dermoscopic differentiation of TI from PP with histopathological correlation. Materials and Methods: This was a cross-sectional study. Cases of PP and TI were included. DermLite 3 was employed. Potassium hydroxide (10%) mount and histopathological examination were done to confirm the diagnosis. Statistical analysis was done using "z" test. Results: A total of 20 TI and ten PP patients were in the study. Micropustules and scales were seen in all (100%) patients of PP and TI. Brown and black globules and hair changes were seen only in TI (100%), not in PP (0.0%). Red dots were observed in all PP patients (100%), not in TI (0.0%). Erythematous background in PP (100%) and in TI (70%) was statistically significant with P < 0.001. Conclusion: Dermoscopy is an in vivo tool to visualize the deeper structures of the skin. It demonstrates characteristic and different patterns in PP and TI as well, thus aiding in the differentiation of both the conditions. It would help treating physician to manage correctly and avoid unnecessary delay in the accurate diagnosis and treatment.